2007
DOI: 10.1111/j.1365-2141.2007.06578.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of ras and bcr‐abl signalling pathways in chronic myeloid leukaemia: a phase I/II study in patients in complete haematological remission

Abstract: of BCR-ABL transcripts and bone marrow cytogenetics. Addition of zoledronic acid to imatinib caused no haematological toxicity. There were no grade III or IV non-haematological adverse effects. Grade I fatigue, hypocalcaemia and fever were common side effects. No responses were demonstrated after 6 months on the combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…On the basis of these preclinical studies, a phase I/II study was designed to assess the safety and efficacy of the combination of zoledronic acid with imatinib in 10 CML patients with a suboptimal response to imatinib alone. Although there was no haematological toxicity, no responses were demonstrated on the combination after 6 months [34]. These results were explained by low plasma concentrations of zoledronic acid, which were probably 10-to 100-fold less than the levels required to inhibit the cell growth or induce apoptosis in vitro, as previously reported [33].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…On the basis of these preclinical studies, a phase I/II study was designed to assess the safety and efficacy of the combination of zoledronic acid with imatinib in 10 CML patients with a suboptimal response to imatinib alone. Although there was no haematological toxicity, no responses were demonstrated on the combination after 6 months [34]. These results were explained by low plasma concentrations of zoledronic acid, which were probably 10-to 100-fold less than the levels required to inhibit the cell growth or induce apoptosis in vitro, as previously reported [33].…”
Section: Discussionsupporting
confidence: 66%
“…These results were explained by low plasma concentrations of zoledronic acid, which were probably 10-to 100-fold less than the levels required to inhibit the cell growth or induce apoptosis in vitro, as previously reported [33]. With the support of several studies that showed tolerable toxicity using the dose of 16 mg administered every 28 days, it was suggested that increasing the dose of zoledronic acid might be effective [34][35][36]. Further largescale clinical trials with escalated doses shall be designed to assess the factual antileukemic efficacy of zoledronic acid in CML patients.…”
Section: Discussionsupporting
confidence: 62%
“…The Ras/ Raf/MAP/extracellular signal-regulated kinase (ERK) pathway often contributes in sensitivity and resistance to leukemia chemotherapy and abnormal expression of this pathway may cause drug resistance during leukemia therapy. For example failing or losing response to imatinib drug in CML patients may be due to RAS mutation (Pavlu et al, 2007). Therefore, detection and controlling the expression of this pathway could improve chemotrapy treatment in leukemia (Steelman et al, 2011;Stoppa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%